The Impact of High-Fat Diet and Restrictive Feeding on Natural Killer Cells in Obese-Resistant BALB/c Mice - Spielmann, Julia; Naujoks, Wiebke; Emde, Matthias; Allweyer, Martin; Fänder, Johannes; Kielstein, Heike; Quandt, Dagmar; Bähr, Ina (Frontiers in Nutrition, 2021)
Background: Obesity is associated with an increased risk for severe infections and various cancer types. Natural killer (NK) cells are circulating lymphoid cells and promoters of the immune response towards viruses and malignant cells. Previous studies demonstrate an impaired phenotype and functionality of NK cells in obesity. So far, the majority of animal studies were exclusively performed using ad libitum feeding regimes and it remained unclear whether NK cell alterations are mediated by obesity-associated immunological changes or by direct effects of the dietary composition. Therefore, the aim of the present study was to characterize NK cells in the peripheral blood of obese-resistant BALB/c mice fed a normal-fat diet (NFD) or high-fat diet (HFD), ad libitum or in a restrictive feeding regime. Methods: Twenty-eight BALB/c-mice were fed a NFD or HFD either ad libitum or in a restrictive manner with 90% of the mean daily food intake of the corresponding ad libitum group (each group n = 7). Blood and visceral adipose tissue were collected for flow cytometric analysis, analysis of plasma cytokine concentrations by multiplex immunoassay and Real-time RT-PCR analyses. For statistical analyses two-way ANOVA with the main factors “feeding regime” and “diet” was performed and to compare means of the four mouse groups post-hoc Tukey’s multiple comparison test was used. Results: Ad libitum-feeding of a HFD in BALB/c mice has no influence on body weight gain, visceral fat mass, plasma cytokine concentrations, immune cell populations as well as the number, frequency and phenotype of NK cells. In contrast, restrictive feeding of a HFD compared to NFD led to significantly higher body weights, visceral fat mass and plasma interferon-γ concentrations which was associated with changes in the frequencies of granulocytes and NK cell subsets as well as in the surface expression of NK cell maturation markers. Conclusion: Results demonstrate for the first time that HFD-induced alterations in NK cells are consequences of the obese associated immunological profile rather than a direct effect of the dietary composition. These data can help to clarify the increased risk for cancer and severe infections in obesity.